Supporting Knowledge Transfer on Functional Significance of Forest Biodiversity - Radl Alfred; Vacik Harald (Information)
The FunDivEurope (Functional Significance of Forest Biodiversity in Europe) project aimed to quantify the role of forest biodiversity for ecosystem functioning and the delivery of goods and services in major European forest types. Members of the research community aimed to communicate the research findings related to the functional significance of forest biodiversity to the wider public. Therefore, a web-based Knowledge Transfer Platform (KTP) was designed to ensure project-generated knowledge is transferred to targeted stakeholders and user groups. The paper shows a user experience-based approach in the development of the knowledge transfer platform, and provides insights into the system architecture to show how semantic web-based technologies are able to target a broader audience while keeping entry barriers as low as possible to support communities of practice to grow.